High night‐time humidity and dissolved organic carbon content support rapid decomposition of standing litter in a semi‐arid landscape. (28th March 2017) - Wang, Jing; Liu, Lingli; Wang, Xin; Yang, Sen; Zhang, Beibei; Li, Ping; Qiao, Chunlian; Deng, Meifeng; Liu, Weixing
Summary: Litter in arid and semi‐arid ecosystems usually exhibits a prolonged standing dead phase after senescence; however, we know little about the ways in which abiotic and microbial processes affect standing litter decomposition. We conducted a 26‐month in situ decomposition experiment in a steppe to investigate the potential mechanisms governing the decomposition of standing litter, and a 192‐day laboratory incubation experiment to further explore the impacts of the standing dead stage on the subsequent litter decomposition and soil organic carbon (SOC) formation after the litter falls to the soil surface. Compared with soil surface litter, standing litter has higher dissolved organic carbon (DOC) content. Standing litter also experienced higher night‐time relative humidity on its surface, which enhanced litter moisture content. The higher DOC concentration, combined with the greater night‐time moisture content, stimulated more microbial activity in standing litter. The decomposition rate ( k ) of standing litter was 92% higher than that of soil surface litter. Moreover, the standing phase conditioned the litter, leading to more rapid decomposition after the litter fell to the soil surface, and increasing the efficiency with which the litter formed SOC. We conclude that the long‐neglected standing phase greatly determines litter decomposition and soil carbon storage in semi‐arid regions. Accounting for standing litter decomposition is critical for accurately simulating carbon turnover in arid and semi‐arid ecosystems. A lay summary is available for this article. Abstract : Lay Summary